Adsorptive membrane for heavy metal removal: Material, fabrication, and performance. (2022) - Fadila, C.R.; Othman, M.H.D.; Adam, M.R.; Takagi, R.; Yoshioka, T.; Khongnakorn, W.; Rahman, M.A.; Jaafar, J.; Ismail, A.F.
Abstract: The research and development of the adsorptive membrane has received great attention due to its ability to perform high separation for heavy metals removal from wastewater. Adsorptive membrane integrates the adsorption and filtration mechanism in a single separation process. Several natural materials such as chitosan, hydroxyapatite, and cellulose can be used to fabricate the adsorptive membrane and thus, might reduce the fabrication cost. Furthermore, the materials can be easily obtained with facile techniques. Many papers have been published and showed the effectiveness of heavy metals removal with adsorptive membrane. In addition, there are several techniques have been used to fabricate the adsorptive membrane. Despite the effectiveness of heavy metal removal, the studies continue to enhance the antifouling properties and to increase the adsorption capacity of the membrane. Adsorbent materials such as titanium oxide (TiO2 ) and chitosan are discovered to exhibit excellent antifouling properties with higher thermal resistance and adsorption capacity. The antifouling properties are attributed to the enhanced and uniform hydrophilicity of the membrane. Thus, this review deliberates the recent progress of the adsorptive membranes in terms of the materials, fabrication methods, and performance.